Morphological and Morphometric Study of the Supratrochlear Foramen - Silva, F.A.; Silva, T.S.; Souza, P.R.F.B.; Reis, R.S.; Ferreira, M.R.S.; Magalhães, C.P. (Journal of Morphological Sciences, 2018)
Introduction The supratrochlear foramen (SF) is located in the distal portion of the humerus, formed in between the coronoid fossa and the olecranon fossa. Is associated with a narrowing of the medullary canal in the distal humerus, in addition to being a phylogenetic characteristic, more common in ancient populations. The objective was to evaluate the incidence of the supratrochlear foramen, it's shape, dimensions and translucency of the septum.Materials and Methods A total of 141 humerus adults, 72 right and 69 left-handed individuals from the collection of the Human Bone of the Academic Center of Vitória-Brazil. The format was classified as oval, round, irregular and cribriform. The vertical (VD) and transversal (TD) diameter were measured and the translucency of the septum was observed.Results Of the 141 humerus, 19.8% (28) had SF 39.3% (11) on the right side and 60.7% (17) on the left side. The oval was the most recurrent, found in 39% of the cases and the translucency was identified in 78% (110) of the bones. The mean VD was 3.653 mm and 3.492 mm on the right and left sides, respectively. The mean of the TD was 4.853 mm on the right side and 5.427 mm on the left. The area averages were 19.633 ± 20.57 mm2 on the right side and 19.919 ± 19.24 mm2 on the left side.Conclusion The knowledge of SF favors the preoperative procedures of patients with fractures in the distal humerus, necessary for the surgeries in the region.
Keywords: humerus; supratroclear foramen; anatomical variations; radiology; phylogeny